2014
DOI: 10.1021/nl5014458
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Electroresistance and Hysteresis in Nanoclusters

Abstract: The existence of multiple thermodynamically stable isomer states is one of the most fundamental properties of small clusters. This work shows that the conformational dependence of the Coulomb charging energy of a nanocluster leads to a giant electroresistance, where charging induced conformational distortion changes the blockade voltage. The intricate interplay between charging and conformation change is demonstrated in a nanocluster Zn3O4 by combining a first-principles calculation with a temperature-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…In a previous work we predicted that some magnetic molecules exhibit distinct self-capacitance in the high-spin and low-spin states . We also found that charging can drive conformational changes to nanoclusters, which leads to a hysteresis in the current–voltage curve in the Coulomb region; the same phenomena was observed in experiments . In this study we calculated the self-capacitance of Ce 3 Mn 8 III and its derivatives.…”
Section: Introductionsupporting
confidence: 68%
“…In a previous work we predicted that some magnetic molecules exhibit distinct self-capacitance in the high-spin and low-spin states . We also found that charging can drive conformational changes to nanoclusters, which leads to a hysteresis in the current–voltage curve in the Coulomb region; the same phenomena was observed in experiments . In this study we calculated the self-capacitance of Ce 3 Mn 8 III and its derivatives.…”
Section: Introductionsupporting
confidence: 68%
“…As we know, any cluster deformation can change its energy level, which determines the region of Coulomb blockade voltage. This principle has also been used theoretically in Li's work in a Zn 3 O 4 cluster device [88].…”
Section: Single Electron Transistors (Sets) Based On a Singlementioning
confidence: 96%
“…21,26 Switching the dipole moment of an SMM can modify its structural and electronic configuration. 27 There are several dipole-switching mechanisms in different SMMs, including ferroelectric polarization, 28 asymmetric metal electrode screening, 29 carrier trapping/detrapping, 30,31 and dipole−electric field interaction. 32 Intramolecular electron transfer is another way a molecule can switch its dipole moment.…”
Section: Introductionmentioning
confidence: 99%